2011
DOI: 10.1111/j.1533-2500.2011.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Multimechanistic Postoperative Analgesia: A Rationale for Transitioning from Intravenous Acetaminophen and Opioids to Oral Formulations

Abstract: Good surgical outcomes depend in part on good pain relief, allowing for early mobilization, optimal recovery, and patient satisfaction. Postsurgical pain has multiple mechanisms, and multimechanistic approaches to postoperative analgesia are recommended and may be associated with improved pain relief, lowered opioid doses, and sometimes a lower rate of opioid-associated side effects. Acetaminophen (paracetamol) is a familiar agent for treating many types of pain, including postsurgical pain. Oral acetaminophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 118 publications
0
24
0
Order By: Relevance
“…Multiple studies have shown reduced pain scores and decreased postoperative opiate consumption in surgical patients receiving either formulation of acetaminophen when used as a component of a multimodal approach in various surgical settings [3, 6, 16]. A majority of these studies administered acetaminophen pre-operatively, whereas in our study, it was administered postoperatively.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple studies have shown reduced pain scores and decreased postoperative opiate consumption in surgical patients receiving either formulation of acetaminophen when used as a component of a multimodal approach in various surgical settings [3, 6, 16]. A majority of these studies administered acetaminophen pre-operatively, whereas in our study, it was administered postoperatively.…”
Section: Discussionmentioning
confidence: 91%
“…20. Additionally, IV acetaminophen does not undergo first-pass metabolism in the liver, reducing hepatic exposure to acetaminophen and thus diminishing the potential for hepatic injury 16,19,21…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the ASA guidelines, other sources have advocated for a multimodal approach to postoperative analgesia. 13,14 Intravenous (IV) acetaminophen is one of the medications utilized in a multimodal analgesia regimen. 15 Acetaminophen has long been available in the United States as an oral or rectal formulation.…”
Section: Impact Of Intraoperative Acetaminophen On Opioid Consumptionmentioning
confidence: 99%